2023
DOI: 10.1029/2022gl102348
|View full text |Cite
|
Sign up to set email alerts
|

Time of Emergence for Altimetry‐Based Significant Wave Height Changes in the North Atlantic

Abstract: Satellite observations of significant wave height (Hs) have recently reached 30 years of continuous record. Is this length sufficient to detect the effect of anthropogenically forced climate change on wave height trends? Wave height decadal variability is influenced by a combination of internal variability and forced variability caused by both anthropogenic and natural forcing. Using a statistical model to derive Hs from sea level pressure field and exploiting ERA‐5 reanalysis data as well as 80 members of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Microseism-based wave state studies spanning shorter timescales than presented here have identified spatiotemporal trends in storm intensity, duration, and tracking 22 – 26 , and have been applied to estimate high-latitude sea ice variations and associated ocean wave attenuation 27 , 28 . Wave state is modulated by inter-annual climate processes 14 , 29 31 and extreme microseism intensity associations, particularly with El Niño (ENSO) states, have previously been noted using shorter duration data sets 25 . However, global evidence for widespread secular intensification of microseism amplitudes has not been previously documented.…”
Section: Introductionmentioning
confidence: 83%
“…Microseism-based wave state studies spanning shorter timescales than presented here have identified spatiotemporal trends in storm intensity, duration, and tracking 22 – 26 , and have been applied to estimate high-latitude sea ice variations and associated ocean wave attenuation 27 , 28 . Wave state is modulated by inter-annual climate processes 14 , 29 31 and extreme microseism intensity associations, particularly with El Niño (ENSO) states, have previously been noted using shorter duration data sets 25 . However, global evidence for widespread secular intensification of microseism amplitudes has not been previously documented.…”
Section: Introductionmentioning
confidence: 83%
“…In this context, comparing unforced CTL variability with forced simulation from CMIP5 (Taylor et al, 2012) framework, Dobrynin et al (2015) could detect climate change signal in wave climate simulations as early as 2010-2020 decade over various regions of global ocean, such as North Atlantic, equatorial Pacific, and Southern Ocean. Another study by Hochet et al (2023) estimated that the date of emergence (when climate change emerges from the noise of natural climate variability) of forced variability in satellite-based wave climate data records would be after 2050 in the North Atlantic. The role of internal variability on wave height trend was evaluated by a recent study (Casas-Prat et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Hochet et al. (2023) estimated that the date of emergence (when climate change emerges from the noise of natural climate variability) of forced variability in satellite‐based wave climate data records would be after 2050 in the North Atlantic. The role of internal variability on wave height trend was evaluated by a recent study (Casas‐Prat et al., 2022).…”
Section: Introductionmentioning
confidence: 99%